1991
DOI: 10.1073/pnas.88.7.2961
|View full text |Cite
|
Sign up to set email alerts
|

Anterior pituitary hormone control by interleukin 2.

Abstract: Several monokines, proteins secreted by monocytes and macrophages, alter release of hormones from the anterior pituitary. We report here the ability offemtomolar concentrations of interleukin 2 (IL-2), a lymphokine released from T lymphocytes, to alter directly pituitary hormone release. The effects of concentrations of IL-2 ranging from 10-i7 to 10-9 M on anterior pituitary hormone release were evaluated in vitro. Hemipituitaries were preincubated in 1 ml of KrebsRinger bicarbonate buffer (KRB) followed by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
48
0
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(57 citation statements)
references
References 37 publications
8
48
0
1
Order By: Relevance
“…First, in response to IL-2 administration, over time, there appears to be an enhancement of ACTH response. This increasing ACTH secretion is congruent with previous preclinical and clinical studies showing that IL-2 administration is associated with activation of stress-responsive neuroendocrine pathways [corticotropin releasing hormone (CRH) and HPA axis] (Butler et al, 1989;Denicoff et al, 1987;Hanisch et al, 1994;Karanth and McCann, 1991;Katahira et al, 1998;Raab et al, 1999;Raber et al, 1995;Spina et al, 1994). We postulate that this enhanced ACTH response may be related to IL-2-induced dysregulation of glucocorticoid receptor function at the level of the pituitary, hypothalamus, and/or hippocampus (Raison and Miller, 2003a) and possibly due to interactions between glucocorticoid receptors and innate immune signaling pathways and/or activation of T-cell responses involving DNA binding of nuclear factor of activated T cells and activation protein-1.…”
Section: Discussionsupporting
confidence: 77%
“…First, in response to IL-2 administration, over time, there appears to be an enhancement of ACTH response. This increasing ACTH secretion is congruent with previous preclinical and clinical studies showing that IL-2 administration is associated with activation of stress-responsive neuroendocrine pathways [corticotropin releasing hormone (CRH) and HPA axis] (Butler et al, 1989;Denicoff et al, 1987;Hanisch et al, 1994;Karanth and McCann, 1991;Katahira et al, 1998;Raab et al, 1999;Raber et al, 1995;Spina et al, 1994). We postulate that this enhanced ACTH response may be related to IL-2-induced dysregulation of glucocorticoid receptor function at the level of the pituitary, hypothalamus, and/or hippocampus (Raison and Miller, 2003a) and possibly due to interactions between glucocorticoid receptors and innate immune signaling pathways and/or activation of T-cell responses involving DNA binding of nuclear factor of activated T cells and activation protein-1.…”
Section: Discussionsupporting
confidence: 77%
“…Karanth and McCann reported the ability of IL-2 to modulate the release of anterior pituitary hormones by a direct action on hemipituitaries incubated in vitro. They indicated that IL-2 augmented the basal release of PRL, TSH and ACTH and attenuated the basal release of LH, FSH and CH [17]. In the present study, we demonstrate the opposite effect of IL-2.…”
Section: Resultssupporting
confidence: 54%
“…There is increasing evidence that interleukins directly act at the pituitary level to modulate the release of anterior pituitary hormones [1,7,8,12,17]. Numerous in vitro studies have addressed the direct effects-with confusing results [1].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various hormones may influence lymphocyte function (1). Conversely, secretory products of macrophages and lymphocytes modulate endocrine function (3)(4)(5)(6)(7)(8). Interleukin-6 (IL-6), for example, is produced by the anterior pituitary (9-11).…”
Section: Introductionmentioning
confidence: 99%